1984
DOI: 10.1159/000183225
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxic Effects of Aminoglycoside Treatment on Renal Protein Reabsorption and Accumulation

Abstract: To quantify the effects of gentamicin, kanamycin and netilmicin on renal protein reabsorption and accumulation, these drugs were administered to rats intraperitoneally (30 mg/kg/day) for 7, 14 or 21 days. Scanning electron microscopy of the glomerular endothelia, urinary measurements of sodium, potassium, endogenous lysozyme, N-acetyl-β-D-glucosaminidase (NAG) as well as clearance and accumulation experiments after i.v. administration of egg-white lysozyme and measurements of inulin clearance (GFR) were done i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It is well established that rats with streptozotocin-induced DM exhibit a significant proteinuria compared with nondiabetic animals (26, 27), and that protein excretion increases in nondiabetic rats following the administration of gentamicin (27)(28)(29). In 6-hr perfusion studies in vivo, Pattyn et al (25) demonstrated that the renal cortical uptake of gentamicin was reduced in diabetic rats with modest proteinuria in comparison to control animals.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that rats with streptozotocin-induced DM exhibit a significant proteinuria compared with nondiabetic animals (26, 27), and that protein excretion increases in nondiabetic rats following the administration of gentamicin (27)(28)(29). In 6-hr perfusion studies in vivo, Pattyn et al (25) demonstrated that the renal cortical uptake of gentamicin was reduced in diabetic rats with modest proteinuria in comparison to control animals.…”
Section: Discussionmentioning
confidence: 99%
“…In both humans and animals, lysosomal phospholipidosis results in cell necrosis and alterations in epithelial cells of proximal tubules and to a lesser extent in distal tubules and collecting ducts. Cojocel et al (1984[13]) has shown that GM decrease level of glomerular filtration, as well as tubular reabsorption, leading to accumulation of low molecular weight proteins along with increased renal excretion of sodium and potassium. In physiological conditions these proteins are freely filtered in glomerulus and completely reabsorbed in tubules.…”
Section: Tubular Effectsmentioning
confidence: 99%
“…Urinary NAG has been widely used as a marker of renal tubular damage caused by aminoglycosides in rats (20)(21)(22). Plasma (blood sample obtained by cardiac puncture) and urine concentrations of creatinine were determined on Day 0 to calculate the pretreatment creatinine clearance.…”
Section: Methodsmentioning
confidence: 99%